MASALAH GIZI DAN PENYAKIT MENULAR PASCA BENCANA - Imran Tumenggung (Jurusan Gizi Politeknik Kesehatan Gorontalo, 2017)
ABSTRACT Indonesia has experienced many natural disasters and manmade disasters that have the potential to affect food and nutrition as well as disease transmission. In fact, Indonesian government has built a system to deal with this problem. However, Indonesia has limited resources to deal with this problem due to the economic crisis, government transition, regional autonomy, decentralization, frequency, nature, and intensity of disasters. Nutrition services and the prevention of infectious diseases for refugees due to disasters are an integral part of overall health services. The goals of food and medical aid, including health workers, are to save the lives of those trapped in crises through the provision of adequate food for life and growth of infants and toddlers. An important issue of food and drug aid for the crisis is the timely and sustainable delivery of adequate quality and quantity to disaster victims. Disaster management teams should be strengthened to anticipate the food and nutrition crisis and the risk of disease transmission from disasters. Knowledge of emergency nutrition, potential infectious diseases, methods and techniques for assessment, monitoring, and evaluation, and the role of health professionals should be improved. Keywords: nutritional problems, infectious diseases, disasters ABSTRAK Indonesia banyak mengalami bencana alam dan bencana buatan manusia yang berpotensi mempengaruhi pangan dan gizi serta penularan penyakit. Sebenarnya, pemerintah Indonesia telah membangun sebuah sistem dalam menangani masalah ini. Namun, Indonesia memiliki keterbatasan sumber daya untuk menangani masalah ini akibat krisis ekonomi, transisi pemerintahan, otonomi daerah, desentralisasi, frekuensi, sifat dan intensitas bencana. Pelayanan gizi dan penanggulangan penyakit menular untuk para pengungsi akibat bencana merupakan bagian integral dari pelayanan kesehatan secara keseluruhan. Tujuan dari bantuan pangan dan obat-obatan termasuk tenaga kesehatan adalah untuk menyelamatkan nyawa mereka yang terjebak dalam krisis melalui pemberian makanan yang cukup untuk kehidupan dan proses pertumbuhan bagi bayi dan anak-anak balita. Isu penting dari bantuanu pangan dan obat-obatan untuk krisis adalah pengiriman tepat waktu dan berkelanjutan yang memadai dalam kualitas dan kuantitas kepada korban bencana. Tim penanggulangan bencana harus diperkuat untuk mengantisipasi krisis makanan dan gizi serta risiko penularan penyakit akibat bencana. Pengetahuan tentang gizi darurat, penyakit-penyakit potensial menular, metode dan teknik untuk penilaian, monitroting dan evaluasi, dan peran tenaga kesehatan harus ditingkatkan.